2020
DOI: 10.3390/md18030175
|View full text |Cite
|
Sign up to set email alerts
|

Marine Microalgae, Spirulina maxima-Derived Modified Pectin and Modified Pectin Nanoparticles Modulate the Gut Microbiota and Trigger Immune Responses in Mice

Abstract: This study evaluated the modulation of gut microbiota, immune responses, and gut morphometry in C57BL/6 mice, upon oral administration of S. maxima-derived modified pectin (SmP, 7.5 mg/mL) and pectin nanoparticles (SmPNPs; 7.5 mg/mL). Metagenomics analysis was conducted using fecal samples, and mice duodenum and jejunum were used for analyzing the immune response and gut morphometry, respectively. The results of metagenomics analysis revealed that the abundance of Bacteroidetes in the gut increased in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Inc. Newtown, CT, USA). Sonicated MSmP was centrifuged at 3500 rpm for 15 min to collect MSmPNPs in the supernatant [ 39 ]. The average particle sizes of MSmp and MSmPNPs are 542.4 nm and 78.6 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inc. Newtown, CT, USA). Sonicated MSmP was centrifuged at 3500 rpm for 15 min to collect MSmPNPs in the supernatant [ 39 ]. The average particle sizes of MSmp and MSmPNPs are 542.4 nm and 78.6 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Microalgae Spirulina is a photosynthetic cyanobacterium that has been used to improve reproductive efficiency in in vivo bovine studies [ 33 ]. Recently, S. maxima -based pectin (SmP), and their modified two products namely, modified SmP (MSmP) and its nanoparticles (MSmPNPs) were investigated for different bioactivities in in vitro and in vivo studies [ 37 , 38 , 39 ]. Modification of SmP remarkably enhanced their functionality via physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…( Table 2 ). It was recently demonstrated that the modified pectin from Spirulina maxima modulates the gut microbiota in mice, inducing mucin, IFN-α and IL-6 release, key factors for ICD activation during an inflammatory cascade [ 96 ]. Similarly, the polyunsaturated fatty acids (PUFAs) from Schizochytrium modulate lymphocyte function by targeting plasma membrane molecular organization such as physical properties (compressibility, phospholipid flip-flop, acyl chain packing, elasticity) and chemical properties (lipid domain formation) [ 126 ].…”
Section: Marine Microalgal Compounds Inducing Icd In Cancer Cellsmentioning
confidence: 99%
“…Spirulina modulates several immune functions in the gut and upregulates the expression of the toll-like receptors 2 and 4 (TLR2 and TLR4) in the ileum of aged mice [63]. Spirulina maxima-derived modified pectin modulates gut microbiota and triggers immune responses in mice [64]. The supplementation of algae-derived β-glucan alleviates diarrhea and enhances gut health in E. coli-infected weaned pigs [65].…”
Section: Algae-derived Metabolites For Microbiota-based Therapy and Immunomodulatory Activity Against Sars-cov-2mentioning
confidence: 99%